Nutrição do tomateiro e sua influência no desenvolvimento de ninfas de Bemisia tabaci (GENN.) biótipo B - Oliveira, Marcos Fernandes (2012)
The objective of this work was to evaluate the effect of tomato plants nutrition on the development of B. tabaci (Genn) biotype B. The experiments were carried out in a completely randomized design in a greenhouse at ambient temperature, moisture and photoperiod, at the Escola de Agronomia e Engenharia de Alimentos (EA/UFG), Goiânia, Goiás, Brasil. Each treatment had eight replicates with one plant per pot. Treatments used to test the various contents of earthworm manure were the association of (soil + earthworm manure: 100% + 0%; 80% + 20%; 60% + 40%; 40% + 60%; 20% + 80%, and 0% + 100%. Treatments used to test the N/K rates were: 1/1; 2/1; 4/1; 8/1; 1/2; 1/4, and 1/8. To test the different sources of organic nitrogen, the following treatments were used: chicken manure; earthworm manure; cotton meal; castor beans meal, as well as the mixtures (chicken manure + earthworm manure + cotton meal + castor beans meal. To test the various sources of mineral nitrogen, the following treatments were used: urea, ammonium sulfate; LL®; calcium nitrate and a mixture of fertilizers (urea + ammonium sulfate + Nitro LL® + calcium nitrate). The infestations were performed 40 days after plugs transplant, by releasing 50 couples of B. tabaci biotype B into screen bags, placed in the third or fourth leaf of each plant. One day after infestation 300 eggs were counted and marked on each infested leaf. Ten days after infestation the amount of unviable eggs were evaluated and first ínstar nymphs marked. The analysis of nymphs development was performed 21 days after infestation in the experiment used to test different sources of nitrogen and N/K rates; and, at 30 days after infestation in the experiments used to test the different levels of earthworm manure. B. tabaci nymphs biotype B showed elongation and mortality in that phase, probably due to antibiosis developed by tomato plants: cultivated in earthworm manure only (egg-adult viability 30% and 44% population reduction); fertilization according to N/K 1/8 rate (egg-adult viability 13% and 69% population reduction); fertilized with chicken manure (30% egg-adult viability and 41% population reduction); and, fertilized with calcium nitrate (25% egg-adult viability and 57% population reduction).